Promoting nursing research globally: the writing to improve nursing science (WINS) program. - Sun, Carolyn; Kulage, Kristine M.; Al‐Touby, Salem; Nyamakura, Rudo; Larson, Elaine (International Nursing Review, 2019)
Aim: To test the feasibility of a remote writing programme, Writing to Improve Nursing Science (WINS), for nursing scholars in low‐ and middle‐income countries and assess its impact on scholarly writing and dissemination. Background: The ability to write and publish scholarly manuscripts is critical for successful nursing research careers. Yet, there is a lack of resources to appropriately mentor nurse scholars in this area. This is especially true for low‐ and middle‐income countries with fewer resources and a dearth of doctorally prepared nursing faculty. Introduction: We adapted an existing university‐based writing class to mentor 10 nurse scientists through the writing and publication process utilizing three components: online didactic training, remote one‐to‐one mentorship and an in‐person peer‐reviewed writing workshop. Methods: Ten nurse faculty from 10 countries selected via competitive application developed manuscripts with remote mentorship and online training for 6 months. Then, an in‐person workshop was held to conduct peer reviews of manuscripts. Mentorship continued for an additional year until the manuscript was either published or the participant no longer wished to pursue publication. Results: All participants prepared a manuscript and were trained in manuscript writing, editing, and the peer review and submission process. To date, four manuscripts have been published. Discussion: The Writing to Improve Nursing Science Program is a feasible model to increase publications among nursing faculty or students globally and allow the sharing of resources across countries. Conclusion and implications for nursing policy: Innovative solutions for sharing of intellectual resources, such as this program may contribute to improving the evidence base globally. Nursing research policies should include a mentorship component to increase publications to improve nursing practice and related patient outcomes.